Soundscape Quality in Recreation Areas of Khao Yai National Park in Thailand - YIMPRASERT, Waranya; TEAMPANPONG, Jiraporn; SOMNAM, Kwanjira (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.12.5(53).17, 2021)
Soundscape is an important component of national parks that are established for conserving biodiversity, natural resources and ecological processes, as well as serving tourism to inculcate conservation awareness. Nevertheless, anthropogenic noise from visitors is difficult to control and can disturb wildlife and visitor experiences. This study aims to illustrate the quality of soundscape in recreational areas of Khao Yai National Park (KYNP) based on soundscape components, sound pressure level, perception and the satisfaction of visitors on soundscape, and satisfaction on Sound pressure level in term of LAeq (dBA). Significant differences in the overall soundscape components, sound pressure level, perception and satisfaction on soundscape and satisfaction on sound pressure level at each recreational area were found. Noise from tourism also impacted the presence of wildlife in recreational areas. A correlation was identified between a higher nature-based experience and higher satisfaction on biophony and geophony. Soundscape satisfaction was influenced by satisfaction on sound pressure level, perceived soundscape, and some demographical factors (gender, the day of visit, hometown, recreational areas, visit frequency, income, education, and occupation). KYNP must monitor soundscape components, soundscape satisfaction, and sound pressure levels to maintain the quality of natural soundscape and visitor experiences in the recreational areas. Further research is recommended on using the proportion of soundscape components and sound pressure level as a key monitoring tool to determine the practical carrying capacity of tourists, as soundscape components can be changed due to sound pressure level and also affect the soundscape satisfaction of tourists.